Exploring the complexity of policy enactment through stories: A sociomaterial informed study. - Burm, Sarah (Scholarship@Western, 2016)
This qualitative research study explores the meaning(s) Aboriginal education leads and school board administrators give to the Ontario First Nations, Métis and Inuit (FNMI) Policy Framework (hereafter referred to as the Framework) and how these meaning(s) are negotiated, storied, and enacted to produce particular processes, outcomes, and effects within the context of Aboriginal education in Ontario. The principles of Critical Narrative Research (CNR) combined with the sensibilities of Actor Network Theory (ANT) are drawn on to foreground the policy actors involved in the implementation of the Framework. Recruitment of research participants took place across both public and Catholic school boards in Ontario, Canada. Qualitative narrative methods were employed to collect data from 13 Aboriginal and non-Aboriginal education leads and school board administrators who are or were previously involved in initiatives aimed at meeting the primary objectives outlined in the Framework. Analysis of data reveals some inconsistency between the values espoused at the Ministry level and what becomes enacted across provincial school boards. Participants identified a number of factors that influenced the extent to which their individual school board delivered programs, services, and supports to build the capacity of both Aboriginal and non-Aboriginal students and staff. Depending on how these factors intersected with one another, the resulting actions produced both productive and destructive effects, sometimes concurrently. An interrogation of discourses around educational achievement is made prominent throughout this study, demonstrating how knowledge and learning is generated through the process and effects of social and material forces coming together.